Uji Pupuk UZAAKH terhadap pH, N-total, dan Timbal Terlarut pada Lahan Sawah Tercemar Limbah Tekstil - Rija Sudirja; Anni Yuniarti; Emma Trinurani; Santi Rosniawaty (Fakultas Pertanian Universitas Padjadjaran, 2018)
ABSTRACT Textile industry waste decreased environment quality, including agricultural soils. This condition caused the degradationof rice field irrigated with contaminated waste water. Rice fields in Rancaekek contaminated with heavy metals such as Pb. The presence of heavy metals in soil can be transported to plant tissues, especially when heavy metals are present in soluble form. The aim of the research was to study the effect of various UZAAKH fertilizer dosage on pH, total-N, and availability of Pb in paddy field contaminated with textile waste. The experiment was conducted in the greenhouse of Agriculture Faculty, Universitas Padjadjaran from December 2017 to March 2018. The experiment was arranged in Randomized Block Design (RBD), consisted of six treatments with five replicates: 150 ; 200 ; 250 ; 300 ; 350 kg ha-1 UZAAKH and 250 kg ha-1 Urea. Data were analyzed with analysis of variance (ANOVA) followed by Tukey’s test at 95% confidence level. The result showed significant effect towards pH and availability of Pb in soil, but negligible differences in Ntotal.Keywords : contaminant soils, heavy metal, textile waste, UZAAKH fertilizer